Association between ambient temperature and semen quality among sperm donation volunteers in South China. (March 2023) - Zhang, Xinzong; Fan, Zhaoyu; Wang, Qiling; Deng, Xinyi; Xu, Ruijun; Li, Yingxin; Liu, Tingting; Wang, Rui; Shi, Chunxiang; Huang, Suli; Lv, Ziquan; Chen, Gongbo; et al.
Graphical abstract: Highlights: Higher ambient temperature was associated with a reduction in semen quality in South China. The lag 70–90 day exposure was associated with a reduction in sperm count and morphology. The lag 10–14 day exposure was associated with a reduction in sperm motility. We did not observe adverse effects of cold exposure on semen quality in South China. Abstract: Background: Potential adverse effects of non-optimum temperatures on human semen quality have drawn much concern worldwide; however, the exposure–response relationship remains less understood. Objectives: To quantitatively assess the association between exposure to ambient temperature and semen quality in South China, and to identify potential critical exposure windows. Methods: We conducted a longitudinal study to investigate 11, 050 volunteers who lived in Guangdong province, China and intended to donate sperm in the Guangdong provincial human sperm bank during 2016–2021. Exposure to ambient temperature during 0–90 days before semen collection was assessed by extracting daily temperatures from a validated grid dataset at each subject's residential address. Linear mixed models and linear regression models were used to perform exposure–response analyses. Results: During the study period, the 11, 050 subjects underwent 44, 564 semen analyses. Each 5 °C increase of lag 0–90 day exposure to ambient temperature was approximately linearly associated with a 3.11 (95 % confidence interval [CI]: 2.08, 4.14) × 10 6 /ml, 9.31 (4.83, 13.80) × 10 6, 1.27 % (0.91 %, 1.62 %), 8.20 (5.33, 11.08) × 10 6, 1.37 % (1.01 %, 1.74 %), 8.29 (5.52, 11.06) × 10 6, 0.67 % (0.28 %, 1.05 %), and 4.50 (2.20, 6.80) × 10 6 reduction in sperm concentration, total sperm number, total motility, total motile sperm number, progressive motility, total progressive sperm number, normal forms, and total normal form sperm number, respectively (all p < 0.001), which was not significantly modified by age (all p for effect modification > 0.05). We identified a critical exposure period of 10–14 days before semen collection for sperm motility, and 70–90 days before semen collection for sperm count and morphology. Conclusions: Our study provides consistent evidence that higher ambient temperature was significantly associated with a reduction in semen quality in South China. The findings highlight the needs to reduce high temperature exposures during 3 months before ejaculation to maintain better semen quality.